EFISIENSI PENGELOLAAN SUMBER DAYA DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022 – 2024) - Irene Florensia; Helmy Adam (E-Jurnal Akuntansi TSM, 2026)
This study aims to examine the effect of resource management efficiency on firm value in healthcare sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Based on signaling theory, information on efficiency disclosed through financial statements can serve as a signal to stakeholders regarding a firm’s condition and future prospects. In this study, resource management efficiency is measured using inventory turnover, operating expense ratio, material cost ratio, human resource cost ratio, and cost of goods sold ratio, while firm value is measured using Tobin’s Q ratio. Secondary data in the form of financial statements and annual reports from 26 healthcare companies, resulting in a total of 78 observations, were analyzed using multiple linear regression with IBM SPSS version 25. The results indicate that inventory turnover has a positive effect on firm value. In contrast, the operating expense ratio, human resource cost ratio, and cost of goods sold ratio have a negative effect on firm value, while the material cost ratio does not show a significant effect. These findings suggest that resource management efficiency is associated with firm value in the healthcare sector during the post-pandemic period.